A novel OCRL1 gene mutation in a Turkish child with Lowe syndrome - Kanık, Ali; Kasap-Demir, Belde; Ateşli, Rüya; Eliaçık, Kayı; Yavaşcan, Onder; Helvacı, Mehmet (The Turkish Journal of Pediatrics, 2013)
Oculocerebrorenal syndrome, also known as Lowe syndrome, is an X-linked recessive disorder that predominantly affects males and is characterized by growth and mental retardation, congenital cataract and renal Fanconi syndrome. OCRL1 is the gene responsible for Lowe syndrome and encodes an inositol polyphosphate-5-phosphatase. We present an 11-year-old boy with Lowe syndrome, who had a de novo frameshift mutation in exon 22 that resulted in amino acid substitution and premature codon termination at position 788. This is a new mutation involving the OCRL1 gene in a patient with Lowe syndrome of Turkish origin and expands the mutation spectrum in this disorder.